Winter Habitat Use by Moose, Alces alces, in Central Interior British Columbia - Proulx, Gilbert; Kariz, Rhonda M. (The Canadian Field-Naturalist, 2005)
In central British Columbia, recent epidemics of Mountain Pine Beetle (Dendroctonus ponderosae) have resulted in the use of expansive clearcut areas to remove infested mature and old Lodgepole Pine (Pinus contorta) stands. This study aimed to determine if Moose (Alces alces) use late-successional Lodgepole Pine stands in mid- to late-winter. Moose activity and habitat use was determined during February-March track surveys in 2000 (60 km) and 2001 (55.7 km). In 2000 (69 tracks) and 2001 (313 tracks), Moose track distribution differed significantly (P < 0.05) from random. They were significantly more abundant than predicted in young stands (dominated by Picea spp.), or early seral stages; they were less abundant than predicted in mature and old Lodgepole Pine stands. It is unlikely that harvesting late-successional Lodgepole Pine stands would affect Moose winter habitat supply.